EFL Teachers’ Perceptions Regarding Cultural Awareness in ICT-Based Learning in Indonesian Elementary School Context - Akhmad Sutiyono; Aksendro Maximilian; Galuh Dwi Ajeng (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2023)
The present study aims to explore Indonesian EFL teachers’ perception regarding the ICT (Information and Communications Technology) usage for developing cultural awareness of students as well as improving their English literacy and communication. Even though English subject is not considered as compulsory to be taught in elementary school, there is evidence that English is still being taught either as the local content subject or as the language-medium of instruction. This study employs survey research by administering a questionnaire for elementary school English teachers in Indonesia who have been ever implementing online learning. The result shows that most teachers respond positively on the implementation of ICT in English instructional practice in elementary school. Regarding the cultural content, the participants agree that ICT can be helpful for them to provide interactive digital teaching material, including cultural material for the students. The existence of ICT is helpful for both students and teachers to provide real and authentic teaching materials. Therefore, the use of ICT needs to be promoted to provide cultural awareness in ELT practice to equip young learners to do intercultural communication in the global world